2009
DOI: 10.3923/pjbs.2009.451.454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metoprolol on Systolic and Diastolic Function in Children with Heart Failure

Abstract: The aim of this study was to assess the effect ofmetoprolol on cardiac function in children with heart failure. This randomized double-blind placebo controlled clinical trial was performed in children with heart failure due to left ventricle volume overload structural heart disease such as VSD, PDA, AI and MR who referred to pediatric cardiology clinics in sari in 2007. The patients divided into case and control groups. All cases were matched as viewpoints of age, sex, weight, kinds of primary disease and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[21][22][23][24] The review was later updated to include two additional studies and two conference proceedings. [25][26][27] No significant reduction in mortality or heart transplantation rates was noted in children being treated with b-blockers. Studies with 30 or fewer patients reported symptomatic improvement in heart failure with b-blocker therapy.…”
Section: Combinationmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] The review was later updated to include two additional studies and two conference proceedings. [25][26][27] No significant reduction in mortality or heart transplantation rates was noted in children being treated with b-blockers. Studies with 30 or fewer patients reported symptomatic improvement in heart failure with b-blocker therapy.…”
Section: Combinationmentioning
confidence: 99%
“…In 2009, a Cochrane database review based on randomized controlled clinical trials investigated the effect of β‐blockers (carvedilol and metoprolol) on pediatric congestive heart failure . The review was later updated to include two additional studies and two conference proceedings . No significant reduction in mortality or heart transplantation rates was noted in children being treated with β‐blockers.…”
Section: β‐Blockers For Cardiac Indicationsmentioning
confidence: 99%